Jejuno-colonic anastomosis to restore intestinal continuity in a case of intestinal failure due to type I short bowel syndrome - Suárez-Luna, Luis Ernesto; Malo, Raúl Andrés Troya; Ramirez, Guadalupe Jhoana Vázquez; Quiroga, José González; Reyes, Karina Sánchez (International Journal of Research in Medical Sciences, 2021)
Short bowel syndrome is a rare surgical complication associated with high morbidity and mortality, significant decrease in quality of life and increasing costs to the healthcare system. In some cases, this condition can be mitigated and even reversed if the intestinal transit is restored with a minimum of 75-100 centimeters of small intestine and a segment of the colon. Some of the surgical techniques available within autologous gastrointestinal reconstruction are Serial transverse enteroplasty (STEP), Longitudinal intestinal lengthening (LILT), and as a last resort, intestinal transplantation. We presented a case of intestinal failure due to type I short bowel syndrome who improved in clinical stage from D4 to D2 after intestinal continuity restitution was performed with a jejuno-colonic anastomosis.